Impact of an Interleukin-1 Receptor Antagonist and Erythropoietin on Experimental Myocardial Ischemia/Reperfusion Injury. (2nd May 2012) - Grothusen, Christina; Hagemann, Angelika; Attmann, Tim; Braesen, Jan; Broch, Ole; Cremer, Jochen; Schoettler, Jan
Abstract : Background . Revascularization of infarcted myocardium results in release of inflammatory cytokines mediating myocardial reperfusion injury and heart failure. Blockage of inflammatory pathways dampens myocardial injury and reduces infarct size. We compared the impact of the interleukin-1 receptor antagonist Anakinra and erythropoietin on myocardial ischemia/reperfusion injury. In contrast to others, we hypothesized that drug administration prior to reperfusion reduces myocardial damage. Methods and Results . 12–15 week-old Lewis rats were subjected to myocardial ischemia by a 1 hr occlusion of the left anterior descending coronary artery. After 15 min of ischemia, a single shot of Anakinra (2 mg/kg body weight (bw)) or erythropoietin (5000 IE/kg bw) was administered intravenously. In contrast to erythropoietin, Anakinra decreased infarct size (P < 0.05, N = 4 /group) and troponin T levels (P < 0.05, N = 4 /group). Conclusion . One-time intravenous administration of Anakinra prior to myocardial reperfusion reduces infarct size in experimental ischemia/reperfusion injury. Thus, Anakinra may represent a treatment option in myocardial infarction prior to revascularization.